Myxoid ovaries that resemble malignancy in young girls: a case report - Fajriman, Fajriman; Antonius, Puja Agung; Muhammad, Syammel (Fakultas Kedokteran Universitas Andalas, 2023)
In the most recent publications on Mayer-Rokitansky-KÃ¼ster-Hauser (MRKH)Â Myxoma is a benign tumor that generally occurs in the heart, soft tissue, muscle, skin and bone. But in this case, we present myxoma that occurs primarily in the ovary. Ovarian myxsoma is a rare benign tumor.In this case report, it was found that a 12-year-old girl was brought by her parents to the M. Djamil Hospital in the city of Padang, West Sumatra. After performing the gynecological physical examination and ultrasonography, there was a hypoechoic mass with an indeterminate solid part of the right adnexa, which was suspected of being an ovarian malignancy. Then it was decided to carry out a procedure in the form of a conservative surgical staging laparotomy. The results of the Anatomical Pathology examination confirmed the myxoid ovarian appearance and the patient was decided for regular monitoring.Â